(9n*n)=4+7n

Simple and best practice solution for (9n*n)=4+7n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9n*n)=4+7n equation:


Simplifying
(9n * n) = 4 + 7n

Multiply n * n
(9n2) = 4 + 7n

Solving
(9n2) = 4 + 7n

Solving for variable 'n'.

Reorder the terms:
-4 + -7n + (9n2) = 4 + 7n + -4 + -7n

Reorder the terms:
-4 + -7n + (9n2) = 4 + -4 + 7n + -7n

Combine like terms: 4 + -4 = 0
-4 + -7n + (9n2) = 0 + 7n + -7n
-4 + -7n + (9n2) = 7n + -7n

Combine like terms: 7n + -7n = 0
-4 + -7n + (9n2) = 0

Begin completing the square.  Divide all terms by
9 the coefficient of the squared term: 

Divide each side by '9'.
-0.4444444444 + -0.7777777778n + n2 = 0

Move the constant term to the right:

Add '0.4444444444' to each side of the equation.
-0.4444444444 + -0.7777777778n + 0.4444444444 + n2 = 0 + 0.4444444444

Reorder the terms:
-0.4444444444 + 0.4444444444 + -0.7777777778n + n2 = 0 + 0.4444444444

Combine like terms: -0.4444444444 + 0.4444444444 = 0.0000000000
0.0000000000 + -0.7777777778n + n2 = 0 + 0.4444444444
-0.7777777778n + n2 = 0 + 0.4444444444

Combine like terms: 0 + 0.4444444444 = 0.4444444444
-0.7777777778n + n2 = 0.4444444444

The n term is -0.7777777778n.  Take half its coefficient (-0.3888888889).
Square it (0.1512345679) and add it to both sides.

Add '0.1512345679' to each side of the equation.
-0.7777777778n + 0.1512345679 + n2 = 0.4444444444 + 0.1512345679

Reorder the terms:
0.1512345679 + -0.7777777778n + n2 = 0.4444444444 + 0.1512345679

Combine like terms: 0.4444444444 + 0.1512345679 = 0.5956790123
0.1512345679 + -0.7777777778n + n2 = 0.5956790123

Factor a perfect square on the left side:
((n) + -0.3888888889)((n) + -0.3888888889) = 0.5956790123

Calculate the square root of the right side: 0.771802444

Break this problem into two subproblems by setting 
((n) + -0.3888888889) equal to 0.771802444 and -0.771802444.

Subproblem 1

(n) + -0.3888888889 = 0.771802444 Simplifying (n) + -0.3888888889 = 0.771802444 n + -0.3888888889 = 0.771802444 Reorder the terms: -0.3888888889 + n = 0.771802444 Solving -0.3888888889 + n = 0.771802444 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '0.3888888889' to each side of the equation. -0.3888888889 + 0.3888888889 + n = 0.771802444 + 0.3888888889 Combine like terms: -0.3888888889 + 0.3888888889 = 0.0000000000 0.0000000000 + n = 0.771802444 + 0.3888888889 n = 0.771802444 + 0.3888888889 Combine like terms: 0.771802444 + 0.3888888889 = 1.1606913329 n = 1.1606913329 Simplifying n = 1.1606913329

Subproblem 2

(n) + -0.3888888889 = -0.771802444 Simplifying (n) + -0.3888888889 = -0.771802444 n + -0.3888888889 = -0.771802444 Reorder the terms: -0.3888888889 + n = -0.771802444 Solving -0.3888888889 + n = -0.771802444 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '0.3888888889' to each side of the equation. -0.3888888889 + 0.3888888889 + n = -0.771802444 + 0.3888888889 Combine like terms: -0.3888888889 + 0.3888888889 = 0.0000000000 0.0000000000 + n = -0.771802444 + 0.3888888889 n = -0.771802444 + 0.3888888889 Combine like terms: -0.771802444 + 0.3888888889 = -0.3829135551 n = -0.3829135551 Simplifying n = -0.3829135551

Solution

The solution to the problem is based on the solutions from the subproblems. n = {1.1606913329, -0.3829135551}

See similar equations:

| 2x-2y-2=0 | | Log(x)=1.3 | | logx=1.3 | | 2(x-1)=26.4 | | a^2+a-3a-3=0 | | ln(2x)=7 | | 2t^2-12t-25=0 | | -6+x=.6x-2.2+2 | | X+4=9+2x | | 35x-23=17 | | y=-5x+10 | | 0=6x+x^2+9 | | 7x-28=21 | | y=x+50 | | 3x+5=9x-(5-2x) | | x-(3x+1)=2x-(4x+3)-x | | 7p+12=13+6p | | 12-4x-x^2=36-16x^2+16 | | 2+10= | | -5.2x-3.3=22.7 | | 10y+2=7 | | 2*d=5d | | 4[-2(4x+3)+2(5x-5)]= | | 9y+(-3y-5)=4y-7 | | 2m(4m)= | | 2m(11n)= | | 2m(11n+3)= | | 0.4x+5.2=4.6 | | 9(2x-4)=3(6x+1) | | x^2-11x-7=0 | | 4t+3=2t+11 | | 4-9x=-11x |

Equations solver categories